Seasonal and Spatial Variations of Bacterial Community Structure in the Bailang River Estuary - Dong, Wenxun; Cui, Zhengguo; Zhao, Mengjuan; Li, Junfeng (Journal of marine science and engineering, 2023)
Planktonic cells are a vital part of biogeochemical nutrient cycling and play an extremely important role in maintaining the balance of water ecosystems. In this study, surface water samples were collected in three seasons (spring, summer, and winter) 10 km along the estuary of the Bailang River to assess the relationship between environmental factors and the bacterial community structure, which was determined by high-throughput sequencing. The physicochemical properties of the samples, including the pH, salinity, and inorganic nitrogen (NH4+, NO3−, and NO2−), exhibited significant seasonal variations, and the diversity and structure of the bacterial community also varied seasonally. A redundancy analysis showed that the inorganic nitrogen (NH4+, NO3−, NO2−), pH, and salinity are key factors in shaping the bacterial community composition. Among the different seasons, the core taxa of bacterial communities were the same, and Actinobacteria, Cyanobacteria, and Proteobacteria were the key components during the three seasons. The bacterial diversity and structure also varied seasonally, but there were no significant differences in spatial composition. Based on a phylogenetic investigation of communities by reconstruction of unobserved states analysis, nitrogen-cycle-related processes include four dominant processes: nitrogen mineralization, nitrogen fixation, dissimilatory nitrate reduction, and denitrification. These results suggest that the bacterial community structure in the waters of the Bailang River estuary is subject to seasonal rather than spatial variation. These findings provide new evidence for studies of the seasonal variation of bacterial communities in estuaries.